2019
DOI: 10.1021/acs.jmedchem.9b01155
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Second-Generation NLRP3 Inflammasome Inhibitors: Design, Synthesis, and Biological Characterization

Abstract: NLRP3 inflammasome has recently emerged as an attractive drug target for neurodegenerative disorders. In our continuing studies, a new chemical scaffold was designed as selective inhibitors of NLRP3 inflammasome. Initial characterization of the lead HL16 demonstrated improved however non-selective inhibition on the NLRP3 inflammasome. Structure-activity relationship studies of HL16 identified a new lead, 17 (YQ128), with an IC 50 of 0.30 ± 0.01 μM. Further studies from in vitro and in vivo models confirmed its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Other NLRP3 inhibitors have been developed that directly target the NACHT domain, including CY-09, Oridonin, Tranilast, OLT1177 and MNS [ 50 , 51 , 52 , 53 ]. Other compounds inhibit the activation of the NLRP3 inflammasome via indirect mechanisms, either by blocking other components of the inflammasome complex or by inhibiting the signaling cascade leading to NLRP3 activation [ 54 , 55 , 56 , 57 , 58 ]. Very recently, it has been reported that targeting the PYD domain may represent an effective strategy for NLRP3 inhibition [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other NLRP3 inhibitors have been developed that directly target the NACHT domain, including CY-09, Oridonin, Tranilast, OLT1177 and MNS [ 50 , 51 , 52 , 53 ]. Other compounds inhibit the activation of the NLRP3 inflammasome via indirect mechanisms, either by blocking other components of the inflammasome complex or by inhibiting the signaling cascade leading to NLRP3 activation [ 54 , 55 , 56 , 57 , 58 ]. Very recently, it has been reported that targeting the PYD domain may represent an effective strategy for NLRP3 inhibition [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that amphenmulin is a fast eliminating drug with the short T1/2 and MRT for three administration routes. The Cmax of amphenmulin after oral administration is significantly lower than that of intraperitoneal injection, which may be due to the obvious first-pass effect of the drug [28]. The Tmax of intraperitoneal injection was shorter than that of oral administration, indicating that the absorption of intraperitoneal administration was faster than that of oral administration.…”
Section: Discussionmentioning
confidence: 93%
“…Compound 17 (YQ128) identified from HL16 is a selective inhibitor of the NLRP3 inflammasome ( Jiang et al., 2019 ). As it can cross the blood-brain barrier in vitro and in vivo and is unlikely to be affected by efflux transport, it demonstrates potential as a treatment for central nervous system diseases ( Jiang et al., 2019 ).…”
Section: Specific Inhibitors Of Nlrp3 Inflammasomementioning
confidence: 99%
“…Compound 17 (YQ128) identified from HL16 is a selective inhibitor of the NLRP3 inflammasome ( Jiang et al., 2019 ). As it can cross the blood-brain barrier in vitro and in vivo and is unlikely to be affected by efflux transport, it demonstrates potential as a treatment for central nervous system diseases ( Jiang et al., 2019 ). However, its low oral bioavailability (10%) limits its application in vivo , and further analogue development based on this new chemical scaffold could be possible in the future ( Jiang et al., 2019 ).…”
Section: Specific Inhibitors Of Nlrp3 Inflammasomementioning
confidence: 99%